1997
DOI: 10.1002/(sici)1098-2418(199701/03)10:1/2<205::aid-rsa11>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

On the all-pairs shortest-path algorithm of Moffat and Takaoka

Abstract: We review how to solve the all‐pairs shortest‐path problem in a nonnegatively weighted digraph with n vertices in expected time O(n2 log n). This bound is shown to hold with high probability for a wide class of probability distributions on nonnegatively weighted digraphs. We also prove that, for a large class of probability distributions, Ω(n log n) time is necessary with high probability to compute shortest‐path distances with respect to a single source. © 1997 John Wiley & Sons, Inc. Random Struct. Alg., 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 2 publications
2
10
0
Order By: Relevance
“…Mehlhorn and Priebe [45] proved that for the complete graph with random edge weights every SSSP algorithm has to check at least Ω(n · log n) edges with high probability. Noshita [53] and Goldberg and Tarjan [35] analyzed the expected number of decrease_Key operations in Dijkstra's algorithm; the time bound, however, does not improve on the worstcase complexity of the algorithm.…”
Section: Random Edge Weightsmentioning
confidence: 99%
“…Mehlhorn and Priebe [45] proved that for the complete graph with random edge weights every SSSP algorithm has to check at least Ω(n · log n) edges with high probability. Noshita [53] and Goldberg and Tarjan [35] analyzed the expected number of decrease_Key operations in Dijkstra's algorithm; the time bound, however, does not improve on the worstcase complexity of the algorithm.…”
Section: Random Edge Weightsmentioning
confidence: 99%
“…The fastest algorithms above solve each SSSP problem in O(n log n) expected time. Mehlhorn and Priebe [MP97] showed that for the endpoint independent model, Ω(n log n) expected time is best possible for algorithms that can only access the (sorted) outgoing adjacency lists of the graph.…”
Section: Average Case Resultsmentioning
confidence: 84%
“…Bloniarz [Blo83] improved it to O(n 2 log n log * n). Finally, Moffat and Takaoka [MT87] and Mehlhorn and Priebe [MP97] (see also recent simplifications by Takaoka and Hashim [TH10,Tak13]) improved the running time to O(n 2 log n). All these algorithms, like Dijkstra's and Spira's algorithm use only the outgoing adjacency lists of the graph.…”
Section: Average Case Resultsmentioning
confidence: 99%
See 2 more Smart Citations